How should durable goods firms combine online and mass media advertisements to promote sales? - Chieko Fujisawa; Norihiro Kasuga (International Telecommunications Society (ITS), 2021)
We develop an advertising strategy for durable goods firms applying a dual time-period model while considering three-stage game in a Cournot competition. We assume that firms employ two advertising approaches; one is online advertising, which escalates consumers' willingness to purchase goods and the other is conventional mass media advertising, including television and radio, which presents a limited 'evoked set' of goods. The term evoked set implies that consumers only consider a small group of brands prior to making a purchase. As firms understand the character of each advertisement, sales strategy is devised to target a heterogeneous consumer through advertising. Should firms only choose one type of advertisement or a combination of the two kinds of ads available? In this model we assume that firms directly consider both types of advertising. Our analysis demonstrates that online advertisement raises the total number of consumer-product matches in the competitive equilibrium. We also show that firms combine the two types of advertisement to apply the differing effects of each format. Moreover, firms increase revenue through an appropriate mix of advertising strategy, although the cost of advertising might increase. Regarding the future direction of advertising, we anticipate that the combination of both online and conventional strategies will persist, maintaining the growth of a diverse product market.
Keywords: D15; D43; L13; D82; 330; Durable goods; Online media advertising; mass media advertising; targeting; media strategy